Can the New York Legislature Bring Back Authentication Boards? The Effect of Proposed Legislation on Liability for Art Authenticators - Schechtner, Hannah (The Columbia Journal of Law & the Arts, 2016)
This Note will first lay out how authenticators—particularly authentication boards and artist foundations who author catalogues raisonnés—currently function in the art market, and how the financial stake in authenticity opinions has increased. It will also delineate the existing legal protections and liabilities that apply to authenticators, and how these liabilities have likely increased due to recent court decisions in New York. In Part II, this Note will examine how the proposed legislation, as intended, would (or would not) enhance legal protections for authenticators. Finally, this Note will suggest a stronger scheme for protecting authenticators that the legislature could pass, while also recognizing the limitations the New York Legislature faces in addressing the current chilling effect on authenticators.